Ultrafast all-optical tuning of direct-gap semiconductor metasurfaces - Maxim R. Shcherbakov (Nature Portfolio, 2017)
Metasurfaces are not adjustable after fabrication, and a critical challenge is to realise a technique of tuning their optical properties that is both fast and efficient. Here, Shcherbakov et al. realise an ultrafast tunable metasurface with picosecond-scale large absolute reflectance modulation at low pump fluences.